REACTIVE CHANGES IN THE VESSELS OF THE RAT’S DUODENAL MUCOSA IN RESPONSE TO THE EFFECT OF COMPLEX FOOD ADDITIVES - Yeroshenko, G.A.; Grygorenko, A.S.; Shevchenko, K.V.; Lysachenko, O.D.; Sokolenko, V.N.; Khilinska, T.V.; Bilash, V.P.; Solod, A.V. (World of Medicine and Biology, 2021)
The paper presents the findings of the morphometric study on the complex action of food additives on the state of the vessels of the mucous membrane. It has been found that at the early stages of observation, the effect of monosodium glutamate, sodium nitrite and Ponceau 4R led to the lowering of the mean values of the metric parameters of the vessels of the blood microcirculatory bed of the mucous membrane and dilatation of the lumen of larger vessels of the submucous layer. Further development of the inflammatory reaction with edema led to a decrease in the diameters of the lumen of the vessels of the resistance and exchange sections with dilatation of the lumen of the venules, caused hypoxia and dystrophic lesions, followed by restoration of the values, due to compensatory-adaptive responses to irritating factor, though no complete normalization occurred. Changes in the vessels of the submucous layer depended on the state of the vessels of the mucous membrane throughout the experiment.
Keywords: duodenum; vessels; food additives; mucous membrane; rats